“Prostitutes Ask for a Home from the Prime Minister”: Historic Embeddedness and Present Day Political-Societal Ramifications of Prostitution in Turkey - Bezsenyi, Tamás (Magyar Rendészet, 2016)
The main focus of this article is the analysis of the structure of prostitution in Turkey, especially in Istanbul. The one-year empirical research is embedded in the particular legal and historical background to explain the current trends in a comprehensible way. Unfortunately Turkish criminology and sociology still neglect the field of legal and illegal forms of today’s prostitution. The Turkish government is working on the dismantling of the remnants of the legal Turkish prostitution industry. This is paradoxical, since illegal prostitution is much more competitive, popular and lucrative. The strict rules of legal prostitution make it less competitive.